Does temporal variability of winter Common Cranes in the dehesas depend on farming practices? - Aviles, J. M.; Medina, F. J.; Sánchez, J. M.; Parejo, D. (Waterbirds, 2002)
The inclusion of Spain and Portugal within the European Community has brought about a change in the traditional farming practices in the dehesas of Iberia to intensive cereal and to irrigated crops. Here we use seven-year counts of Common Cranes in 38 wintering sites to evaluate whether habitat structure modified by farm- ing practices in the Holm Oak (Quercus ilex) dehesas is an important determinant of variability in winter crane num- bers. We extracted, from a set of nine variables that express different levels of human management in the Holm Oak dehesas, two factors that accounted for the 66% of the variance. The first factor was related to livestock utiliza- tion of the dehesas, while the second one reflected Holm Oak presence. We ran a general linear model to analyze the influence of farming practices (PC1 and PC2), landscape heterogeneity and roost site stability on inter- and in- tra-season variability in numbers of winter cranes. Livestock presence, Holm Oak presence, landscape heterogeneity and roost type stability did not explain intra- and inter- season variability in crane numbers wintering in the Holm Oak dehesas of Spain.
Keywords: Agricultural intensification; Common Crane; Grus grus; holm oak dehesas; southwestern Spain; winter stability